2018
DOI: 10.1002/ldr.3121
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the very fine sand fraction for calculating the soil erodibility K‐factor

Abstract: The K‐factor of the universal soil loss equation is a core component in many erosion models, as a measure of soil erodibility. It can be estimated by a nomograph, where the summed fractions of silt and very fine sand (VFS) are basic inputs. Frequently, only the three broad particle‐size classes of sand, silt, and clay are measured in laboratories; thus, the VFS fraction must be estimated. Three models are currently available for this estimation, namely, (a) the Revised Universal Soil Loss Equation formula, (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A third group of articles presents new methodologies for assessing the impacts of landuse on soil erosion. A statistical‐based method for calculating the soil erodibility factor (K) of RUSLE was developed by Corral‐Pazos‐de‐Provens, Domingo‐Santos, and Rapp‐Arrarás (2018), based on more than 300,000 horizon samples from the United States of America. Mapping and measuring techniques applied by Balaguer‐Puig, Marqués‐Mateu, Lerma, and Ibáñez‐Asensio (2018) and Gudino‐Elizondo et al (2018) present state‐of‐the‐art methods for event‐scale rill and gully erosion analysis, respectively.…”
Section: Timeliness and Relevance Of The Issuementioning
confidence: 99%
“…A third group of articles presents new methodologies for assessing the impacts of landuse on soil erosion. A statistical‐based method for calculating the soil erodibility factor (K) of RUSLE was developed by Corral‐Pazos‐de‐Provens, Domingo‐Santos, and Rapp‐Arrarás (2018), based on more than 300,000 horizon samples from the United States of America. Mapping and measuring techniques applied by Balaguer‐Puig, Marqués‐Mateu, Lerma, and Ibáñez‐Asensio (2018) and Gudino‐Elizondo et al (2018) present state‐of‐the‐art methods for event‐scale rill and gully erosion analysis, respectively.…”
Section: Timeliness and Relevance Of The Issuementioning
confidence: 99%
“…Standard deviation of k-values for the determination of changes in the basin was 0.006; the variation coefficient was 12.367. Many studies have demonstrated that soil erodibility varies with the location, properties of soil, human activities, vegetation types [34][35][36][37]. Therefore, the k-value in the study area was moderately variable because of the differences in soil texture, terrain, vegetation, farming systems, and other factors.…”
Section: Discussionmentioning
confidence: 99%